2020
DOI: 10.30534/ijeter/2020/31832020
|View full text |Cite
|
Sign up to set email alerts
|

Performance of RPL in Healthcare Wireless Sensor Network

Abstract: The new advances of the Internet of Things (IoT) technology can be utilized to promote service delivery in several real-life applications such as the healthcare systems. The Routing Protocol for Low Power and Loss Network (RPL) is a routing protocol designed to serve as a proper routing protocol for packets in Wireless Sensor Networks (WSN). Among the most prominent issues exist in the RPL protocol are packet loss within the WSN and sensors power consumption especially in healthcare WSNs. Multiple Objective Fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As expected, the results show that NullRDC is better in terms of latency, while ContikiMac outperforms the others in terms of power consumption. Al-Shargabi and Aleswid [ 131 ] also utilize the Cooja network simulator to evaluate which OF is more suitable for a WSN in healthcare scenarios. OF0 and ETX are examined in various network topologies, such as the grid and random topology, under diverse densities.…”
Section: Routing For Data Gathering In Wsnmentioning
confidence: 99%
“…As expected, the results show that NullRDC is better in terms of latency, while ContikiMac outperforms the others in terms of power consumption. Al-Shargabi and Aleswid [ 131 ] also utilize the Cooja network simulator to evaluate which OF is more suitable for a WSN in healthcare scenarios. OF0 and ETX are examined in various network topologies, such as the grid and random topology, under diverse densities.…”
Section: Routing For Data Gathering In Wsnmentioning
confidence: 99%
“…In Al‐Shargabi and Aleswid, 19 ETX and OF0 metrics in a WSN healthcare Scenario were evaluated. The topologies that were used in this research were random and grid with diverse RX and it was shown that OF0 is more efficient than ETX in terms of PDR compared to power consumption and therefore in healthcare implementation of RPL such as ICU which the PDR must be high, OF0 is the most used.…”
Section: Related Workmentioning
confidence: 99%
“…Al-Shargabi et al 20 present a WSN based health care system. They deployed the nodes in a rectangular area of 1000 meters square.…”
Section: Related Workmentioning
confidence: 99%